Perancangan Website Pendaftaran dan Penyeleksian Tingkatan sebagai Media Promosi di English Language School Padang - Agung Ramadhanu; Firna Yenila; Arsyah Arsyah; Andry Novrianto; Jehan Harka (Universitas Putra Indonesia YPTK Padang, 2019)
This research describes the online registration Website, which is based on the solutions obtained from the research conducted at English Language School Padang. It was concluded that the old Information System (manual system) used is no longer relevant to the needs of the user, after the study of English Language School Padang by collecting data containing the Problems with the system manual, researchers provide solutions to the problem, by creating a Web Base System (website) that is done by doing the steps in designing the design of output inputs, and processes. The results of the analysis and the stage is applied in the application of the website that is more interactive and relevant to the needs of the user, in conducting their activities.